Management of children with type 1 diabetes during illness: a national survey. Issue 1090 (22nd February 2016) - Soni, Astha; Agwu, Juliana Chizo; Wright, Neil Peter; Moudiotis, Christopher; Kershaw, Melanie; Edge, Julie; Drew, Josephine Helen; Ng, Sze May
Abstract: Aim: Adequate sick-day management at home can reduce the risk of progression to diabetic ketoacidosis and admission to hospital. The aim of this project was to review the management of diabetes during illness. Method: The Association of Children's Diabetes Clinicians (ACDC) carried out a questionnaire survey of all paediatric diabetes units. In addition, parents of children with type 1 diabetes completed an online questionnaire. Results: The survey of 127 units had a 73% response rate. Sick-day management guidelines were in place in 93%. All guidelines advised giving extra insulin during illness. In 67%, the extra dose was based on a fraction of total daily dose. 22% used units per kg body weight (U/kg). 21% used locally derived formulae to calculate extra dose of insulin. 3% of units advised only blood ketone monitoring. Although all units had an out-of-hours access policy for the families, 45% received advice from the general paediatric registrar. Only in 15%, the advice was directly from a member of the paediatric diabetes team. 680 parents completed the questionnaire. 86% reported receiving training on managing sick days. The majority (52.2%) receiving an informal session at diagnosis. 40% did not know what to do in the presence of raised blood glucose and high blood ketones. Conclusions: There was a wide variation in the practice of monitoring and advice given during illness. Both surveys highlight need for national guidance as well and to improve quality of sick-day rule education programmes for parents of children with type 1 diabetes.